Original Contributions to the Chemical Composition, Microbicidal, Virulence-Arresting and Antibiotic-Enhancing Activity of Essential Oils from Four Coniferous Species - Diana-Carolina Visan; Eliza Oprea; Valeria Radulescu; Ion Voiculescu; Iovu-Adrian Biris; Ani Ioana Cotar; Crina Saviuc; Mariana Carmen Chifiriuc; Ioana Cristina Marinas (MDPI AG, 2021)
This study aimed to establish the essential oil (EO) composition from young shoots of Picea abies, Larix decidua, Pseudotsuga menziesii, and Pinus nigra harvested from Romania and evaluate their antimicrobial and anti-virulence activity, as well as potential synergies with currently used antibiotics. The samples' EO average content varied between 0.62% and 1.02% (mL/100 g plant). The mono- and sesquiterpene hydrocarbons were dominant in the composition of the studied EOs. The antimicrobial activity revealed that the minimum inhibitory concentration (MIC) values for the tested EOs and some pure compounds known for their antimicrobial activity ranged from 6.25 to 100 µL/mL. The most intensive antimicrobial effect was obtained for the Pinus nigra EO, which exhibited the best synergistic effect with some antibiotics against Staphylococcus aureus strains (i.e., oxacillin, tetracycline, erythromycin and gentamycin). The subinhibitory concentrations (sMIC) of the coniferous EOs inhibited the expression of soluble virulence factors (DN-ase, lipase, lecithinase, hemolysins, caseinase and siderophore-like), their efficiency being similar to that of the tested pure compounds, and inhibited the rhl gene expression in Pseudomonas aeruginosa, suggesting their virulence-arresting drug potential.